2018
DOI: 10.3389/fendo.2018.00452
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Action in the Ovary

Abstract: Androgen production by the ovary is an essential requirement for normal cyclical secretion of estradiol but its physiological role extends to important actions on both preantral and antral follicle development, including promotion of granulosa cell proliferation. It is likely only in mature antral follicles that androgens encourage apoptosis and consequent follicle atresia, and this may be an important mechanism to ensure mono-follicular ovulation in primates, including humans. Recent studies have provided new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
67
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 84 publications
6
67
0
2
Order By: Relevance
“…In the human, this occurs when follicles are between 4 and 6 mm in diameter (Gougeon class 5 to 6). As will be discussed, the transition from peak androgen dependence also occurs around this same time [ 18 , 24 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the human, this occurs when follicles are between 4 and 6 mm in diameter (Gougeon class 5 to 6). As will be discussed, the transition from peak androgen dependence also occurs around this same time [ 18 , 24 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Although androgens are critical hormones in the pre-antral to early antral follicle’s stage of development, they are not acting alone in promoting follicle growth and development. For example, acting in conjunction with FSH and modulated by IGF-1 and GDF9 (positively) and AMH and BMP15 (negatively), androgens promote granulosa cell proliferation [ 24 ] (Fig. 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Androgens play key roles in a range of reproductive functions necessary for conception, acting directly through the androgen receptor (AR), or as necessary precursors for estrogen synthesis. Androgens are considered to represent a double-edged sword in human follicular development, with positive effects on follicles at preantral and small antral stages and potential negative effects on pre-ovulatory follicles unless appropriate downregulation of granulosa cell AR takes place (1,2). Women with polycystic ovary syndrome (PCOS) are characterized by a high antral follicle count and increased androgen levels, and androgens seem to play an important role in aberrant follicle development and anovulation in this group of women (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Women with PCOS experience higher rates of pregnancy loss compared to non-PCOS women in populations seeking infertility therapy [4], which may be related to poor oocyte quality due to impaired folliculogenesis [5,6]. Studies on nonprimate [7] and primate species [8,9] identified stage-specific effects of excess androgen on follicular development and function. In vitro studies employing three-dimensional culture of macaque follicles suggest that androgen actions are critical for pre-antral folliculogenesis in primates, but once follicles reach the antral stage, continued exposure to elevated androgens results in smaller antral follicles producing less local factors (VEGF, AMH) and steroid (estradiol, E2) compared to controls [9].…”
Section: Introductionmentioning
confidence: 99%